SOSIALISASI PENGARUH TERAPI PSIKORELIGIUS DZIKIR UNTUK MENURUNKAN SALAH SATU TANDA DAN GEJALA DARI SKIZOFRENIA YAITU HALUSINASI PENDENGARAN DIWILAYAH KERJA UPTD PUSKESMAS KONCARA KABUPATEN PURWAKARTA - Yuli Erlina; Suci Hardianti; Efhal Rhevaldy (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2025)
Auditory hallucinations are one of the main symptoms in schizophrenia patients which often cause emotional distress and maladaptive behavior. Psychoreligious approaches such as dhikr therapy are believed to help reduce the intensity of hallucinations by increasing mental peace and spiritual strengthening of patients. To determine the effect of implementing dhikr psychoreligious therapy on reducing the intensity of auditory hallucinations in schizophrenia patients in the working area of ​​the Koncara Community Health Center UPTD, Purwakarta Regency. This community service activity aims to improve the knowledge and skills of nurses at the Koncara Community Health Center in carrying out dhikr psychoreligious therapy to reduce the signs and symptoms of schizophrenia in the Koncara Community Health Center UPTD. The method of implementing the activity uses a lecture, demonstration, and simulation approach. The activity participants were 20 people consisting of implementing nurses and shift managers. Evaluation was carried out using a pre-test and post-test to assess the increase in knowledge, as well as observation of skills during the simulation practice. The results of the activity showed an increase in participants' knowledge from an average value of 58% (pre-test) to 89% (post-test). Furthermore, 90% of participants were able to perform the psychoreligious therapy simulation using the correct techniques. Participants also demonstrated high enthusiasm throughout the entire series of activities. Psychoreligious therapy outreach and training have proven effective in improving the knowledge and skills of nurses at the Koncara Community Service Unit (UPTD PKM). This therapy can be used as a non-pharmacological intervention to support the healing process of patients with mental disorders.